2017
DOI: 10.2176/nmc.tn.2017-0110
|View full text |Cite
|
Sign up to set email alerts
|

Neuronavigation-guided Frameless Stereoelectroencephalography (SEEG)

Abstract: Stereoelectroencephalography (SEEG) is an invasive surgical procedure used to identify epileptogenic zones. The combination of both subdural grids and depth electrodes (DEs) is currently used for invasive intracranial monitoring in many epilepsy centers. To perform DE implantation, some centers use frame-based stereotactic techniques and others use stereotactic robotic techniques. However, not all epilepsy centers have access to these tools. We hypothesized that DE implantation using a neuronavigation system c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Our measured mean TP deviation was 2.7 ± 2.0 mm. With regard to the existing literature, our accuracy results were worse than those achieved by frame-based/robotic-assisted approaches [ 13 , 14 , 20 , 22 – 27 , 34 ] Most groups utilising those implantation techniques report TP deviations in the range of 0.3–6.7 mm [ 14 , 20 , 22 , 24 , 26 , 34 , 36 ]. In-depth analysis of our data revealed that one patient (Pat.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our measured mean TP deviation was 2.7 ± 2.0 mm. With regard to the existing literature, our accuracy results were worse than those achieved by frame-based/robotic-assisted approaches [ 13 , 14 , 20 , 22 – 27 , 34 ] Most groups utilising those implantation techniques report TP deviations in the range of 0.3–6.7 mm [ 14 , 20 , 22 , 24 , 26 , 34 , 36 ]. In-depth analysis of our data revealed that one patient (Pat.…”
Section: Discussionmentioning
confidence: 75%
“…Stereoelectroencephalography techniques are categorised into three distinct technical approaches: frame-based, robot-assisted and frameless surgery (Suppl. Table 2 ) [ 1 , 2 , 4 , 5 , 7 , 9 , 10 , 12 20 , 24 29 , 31 33 , 37 , 38 , 40 43 , 45 – 47 , 49 54 , 58 , 59 , 65 67 ]. Superior accuracy is not only important to ensure diagnostic efficacy, but also correlates with surgical complications such as electrode malpositioning and haemorrhage [ 7 , 11 , 16 , 39 , 43 , 49 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who fulfilled the following criteria were also excluded: (1) patients who received tube feeding; (2) patients who underwent depth electrode placement surgery through burr holes; (3) patients who underwent multiple SEs because the first SE did not cover an appropriate area such as the edge of the grid or a region outside the grid, and then they underwent second or third SEs; (4) patients who exhibited postoperative disturbance of consciousness due to status epilepticus, major complications such as massive subdural hematoma, severe meningitis, or other factors that prevented postoperative nutritional intervention and required prolonged infusion therapy; and (5) patients who were on a ketogenic diet including the classical ketogenic or modified Atkins diet. Patients who underwent burr hole surgery were excluded because this surgery is less invasive than open cranial electrode placement, and there could be differences in intracranial pressure [ 23 ]. Patients who underwent multiple SEs were excluded because we could not simply perform comparisons before and after the introduction of the nutritional intervention for any of these patients who exhibited postoperative disturbance of consciousness.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial errors theoretically do not exist between these structures. 8 We applied this system without surface matching, using a touchless laser pointer for patient registration, and thus accurately measured head slippage.…”
Section: Intraoperative Ctmentioning
confidence: 99%